(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2024)
In this paper, some cases of wave-like equation have been solved by modified new iterative method as an infinite power series but it is impossible to compute the infinite series, therefore, the truncated power series was approximated by Pade approximation. Pade approximation approximates a truncated power series as ratio of two polynomials to reduce calculations and shorten the power series while maintaining accuracy. These cases are shown the successful use of solution approximation by Pade approximation compared to power series expansion.